Quantitative relationship between cladocera and cyanobacteria: A study based on field survey - Li, Daikui; He, Ping; Liu, Cunqi; Xu, Jie; Hou, Liping; Gao, Xiuli; Wang, Dewang; Wang, Jiawen (Frontiers in Ecology and Evolution, 2022)
Cyanobacteria are a functional group of phytoplankton that are prone to bloom and produce algal toxins in slow-flowing water bodies in summer. Cladocera are the functional group of zooplankton with larger bodies and higher grazing efficiency on algae. Studying the quantitative relationship between cyanobacteria and cladocera, especially in unmanipulated and unpredictable natural ecosystems in the wild, provides the key to revealing the mechanism of cyanobacterial blooms and finding effective control and prevention methods. This paper proposes a research method to detect the threshold for cladocera to control cyanobacteria by using the path of “edge scatter-segment regression”. Based on the field survey data from 242 sample sites in shallow and slow-flowing rivers in North China, the quantitative relationship between the main functional groups of zooplankton and phytoplankton was analyzed, and the standard deviation and coefficient of variation were used to test the threshold. This paper finally compares the roles of body size and cladocera abundance in cyanobacteria control. The results showed that in natural ecosystems, cladocera were the best functional group for controlling the abundance of cyanobacteria among zooplankton. The control effect of cladocera on the abundance of cyanobacteria is not linear but nonlinear, and cladocera can only have a stable control effect under certain conditions. The total phosphorus concentrations and water temperatures did not interfere with the analysis results in this paper. In wild ecosystems, the predation process of cladocera on cyanobacteria basically follows the “size-efficiency” hypothesis, but when cladocera successfully control cyanobacterial abundances, it is often due to “win by quantity” rather than “win by size”. The phenomenon of nonlinear variation in the cladocera density-cyanobacteria density relationship fits well with the description of the transition from a stable to chaotic state in chaos theory. This paper reveals the complex quantitative relationships of plankton food chains in wild aquatic ecosystems. The ecological threshold detection of the cladocera-cyanobacterial abundances provides a quantitative basis for early warning, control and prevention of cyanobacteria blooms. The nonlinear variations in cladocera density-cyanobacteria density revealed in this paper provide insight and evidence for understanding the complex changes in aquatic ecosystems.